Effectiveness of the Methods of Internal Financial Control as a Guarantee of Sustainability of Tourism Companies’ Development - YUDINA, Tatiana A.; VANDINA, Olga G.; BOGOVIZ, Aleksei V.; LOBOVA, Svetlana V. (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017, 2017)
The purpose of the work is to study the effectiveness of the methods of internal financial control as a guarantee of sustainable tourism companies’ development in modern Russia. The authors perform comparative analysis of effectiveness of external measures and measures of internal financial control as to sustainability of tourism companies’ development and offer the algorithm of conduct of internal financial control in the interests of effective provision of tourism companies’ sustainability. As a result, the authors substantiate the necessity for search for highly-effective method of solving the problem of provision of sustainable tourism companies’ development in modern Russia and prove that such method is internal financial control, due to which self-limitation of financial risks from the tourism companies will allow keeping their financial indicators at the targeted level. Due to the interest in maximization of result and flexible and adaptive approach to finances management, these methods show high effectiveness as to provision of sustainability of tourism companies’ development.